Growth and Characterization of Bis-L-alanine Picrate (BLAP) Single Crystals - T. H. Freeda3, T. Vela1, P. Selvarajan2* (Journal of Experimental Sciences, 2010)
Bis L-alanine Picrate(BLAP) salt was synthesized and single crystals of BLAP were grown by solution method with slow evaporation technique. Initially, the synthesized salt was subjected to solubility studies and in accordance with the solubility data, the aqueous saturated solution of the synthesized salt was prepared at room temperature for the growth of crystals. Transparent, light-yellow coloured crystals were harvested after a period of 30 days. The grown BLAP crystals were subjected to various studies for the characterization. The crystal structure of the grown crystal was identified by single crystal and powder X-ray Diffraction(XRD) studies. FTIR Study reveals that the functional groups present in the crystal. Its optical properties were examined by UV-Vis-NIR analysis. The Vickers micro hardness values were measured for the grown crystal. SHG generation study was carried out to confirm the NLO activity of grown sample.